Penyeluhan Peningkatan Produksi Pembuatan Sagu di Kelurahan Guraping Kecamatan Oba Utara Kota Tidore Kepulauan - Johan Fahri; Fadhliah M Alhadar; Musdar Muhammad (Universitas Kristen Indonesia Toraja, 2024)
Of the various problems faced by the sago-making group of Guraping village, North Oba sub-district to increase production on a larger scale, namely; pengiringan to make sago still relies on the sun's heat, so that the rainy season sago production is no longer produced. The methods of service are: lectures, practices and mentoring and monitoring, with the outputs produced by the service, namely, publishing the results of the service in national journals, making service videos and publishing service activities in online media. The results of the PKM, sago making in Guraping Village, does not yet have an institution / cooperative, sago making is still individual so that there is no increase in production in the manufacture of sago.